The Effect of Profit-Sharing Financing, NPF, and FDR on the Profitability of BSI in the Post-Merger Period 2021-2024 - Aninda Khoirun Nisa'; Ahmad Sodiq; Resa Nur Laila (CV.RIZANIA MEDIA PRATAMA, 2026)
Profitability is a crucial aspect to consider when assessing the ability of Islamic banks to manage funds based on profit-sharing and sharia principles. In the post-merger period, Bank Syariah Indonesia faced challenges in increasing profitability through financing, managing non-performing financing risks, and controlling liquidity. Previous research has generally focused on Islamic banks in the pre-merger period. Therefore, this study aims to determine the effect of profit-sharing financing, non-performing financing, and the financing-to-deposit ratio on the profitability of Bank Syariah Indonesia for the 2021-2024 period, both partially and simultaneously. This study employed a quantitative approach with Multiple Linear Regression methodology and utilized secondary data from Bank Syariah Indonesia's quarterly financial statements for the 2021-2024 period, with a total of 16 observations using EViews 13. Results: Profit-sharing financing and the financing-to-deposit ratio had no significant effect on profitability, while non-performing financing had a significant negative effect on profitability. Simultaneously, all three significantly impacted profitability. The adjusted R2 value of 84.11% indicates a strong relationship between the three dependent variables and profitability after the Bank Syariah Indonesia merger. Theoretically, this study contributes to the evaluation of risk management at Bank Syariah Indonesia. The managerial implications of this study emphasize the importance of controlling non-performing financing risks to increase profitability.